DOMESTICATING FOOTBALL RIVALRY THROUGH PARTICIPATORY CULTURE: THE DERBY JATENG CASE - Advento, Zena Pio Meidi (Universitas prof. Dr. Moestopo (Beragama), 2025)
This study explores the dynamic rivalry and communication between supporters of Derby Jateng between two football clubs, PSIS Semarang and Persis Solo, in Central Java, Indonesia. Drawing from the theory of Participatory Culture, the research hypothesizes that rivalry and competition among supporters can foster a sense of community, identity, and participatory engagement. The methods used in the study involve in-depth interviews with key informants from both supporter groups, combined with observational data from social media platforms and field observations during matches. The results suggest that despite the intense rivalry, a majority of interactions between the groups are characterized by banter and psywar, creating a participatory culture that extends beyond the football field. There is evidence of mutual respect, maturity, and a sense of brotherhood among the supporters. This unique dynamic is regulated by various stakeholders, including the police, community leaders, clubs, match managing committee, and political figures, who help 'domesticate' the rivalry and maintain peace and order. The study concludes that football rivalry, when managed properly, can serve as a platform for participatory culture, fostering community engagement, identity formation, and social cohesion.